Complete Sequence of a 641-kb Insertion of Mitochondrial DNA in the Arabidopsis thaliana Nuclear Genome. (21st April 2022) - Fields, Peter D.; Waneka, Gus; Naish, Matthew; Schatz, Michael C.; Henderson, Ian R.; Sloan, Daniel B.
Abstract: Intracellular transfers of mitochondrial DNA continue to shape nuclear genomes. Chromosome 2 of the model plant Arabidopsis thaliana contains one of the largest known nuclear insertions of mitochondrial DNA (numts). Estimated at over 600 kb in size, this numt is larger than the entire Arabidopsis mitochondrial genome. The primary Arabidopsis nuclear reference genome contains less than half of the numt because of its structural complexity and repetitiveness. Recent data sets generated with improved long-read sequencing technologies (PacBio HiFi) provide an opportunity to finally determine the accurate sequence and structure of this numt. We performed a de novo assembly using sequencing data from recent initiatives to span the Arabidopsis centromeres, producing a gap-free sequence of the Chromosome 2 numt, which is 641 kb in length and has 99.933% nucleotide sequence identity with the actual mitochondrial genome. The numt assembly is consistent with the repetitive structure previously predicted from fiber-based fluorescent in situ hybridization. Nanopore sequencing data indicate that the numt has high levels of cytosine methylation, helping to explain its biased spectrum of nucleotide sequence divergence and supporting previous inferences that it is transcriptionally inactive. The original numt insertion appears to have involved multiple mitochondrial DNA copies with alternative structures that subsequently underwent an additional duplication event within the nuclear genome. This work provides insights into numt evolution, addresses one of the last unresolved regions of the Arabidopsis reference genome, and represents a resource for distinguishing between highly similar numt and mitochondrial sequences in studies of transcription, epigenetic modifications, and de novo mutations.